Eksploitasi tenaga kerja di kamboja dalam perspektif qs. Al-baqarah: 188 - anjany, Selvia (Maliki Interdisciplinary Journal, 2026)
This study was conducted with the main objective of analyzing the importance of human rights as outlined in the Qur'an and their implications for the phenomenon of labor exploitation, focusing on Indonesian migrant workers in Cambodia. The data used in this study was collected through a literature review. The main sources of data included scientific journals and social media content containing victim testimonies. These sources served as the main basis for the research data collection process. The results of this study show that labor exploitation is the abuse of power to force workers to perform work under unfair and inhumane conditions. From this, we can understand that the Qur'an can minimize the risk of slavery. Human rights, emphasized in the Qur'an, explicitly prohibit the practice of labor exploitation. The Qur'an encourages the enforcement of justice and good treatment of workers, one of which is described through the prohibition of taking property unjustly in Surah Al-Baqarah verse 188.